C# in Depth, Fourth Edition - Skeet, Jon (Manning Publications, 2019)
C# in Depth, Fourth Edition is a revised edition of the bestseller written by C# legend Jon Skeet. This authoritative and engaging guide is your key to unlocking this powerful language, including the new features of C# 6 and 7. In it, Jon introduces expression-bodied members, interpolated strings, pattern matching, and more. Real-world examples drive it all home. By the end of this awesome book, you'll be writing C# code with skill, style, and confidence.
Keywords: C# (Computer program language); C# (Langage de programmation)